2017
DOI: 10.24954/mjecon.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Growth Volatility and Openness in Sub-Saharan Africa

Abstract: There is no a unique agreement regarding the impact of trade openness and financial openness on growth volatility. We carried out an empirical investigation using system GMM to assess the impact of openness on growth volatility in Sub-Saharan African. The analysis considered a panel of 29 countries from 1981 to 2010. According to our results, contrary to earlier findings, both trade and financial openness significantly reduce growth volatility in Sub-Saharan Africa. However, financial openness isn't found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The results also show that the patterns of output volatility are different across countries. Mekonnen and Dogreul, (2017) empirically assessed the impact of openness on growth volatility in 29 Sub-Saharan African countries. Using data from 1981 to 2010 and system GMM method their results showed that both trade and financial openness significantly reduce growth volatility in Sub-Saharan Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results also show that the patterns of output volatility are different across countries. Mekonnen and Dogreul, (2017) empirically assessed the impact of openness on growth volatility in 29 Sub-Saharan African countries. Using data from 1981 to 2010 and system GMM method their results showed that both trade and financial openness significantly reduce growth volatility in Sub-Saharan Africa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More financially open countries experience greater reduction in growth volatility following equity market opening. Mekonnen and Dogruel (2017) investigate the effect of financial openness and trade openness on growth volatility in a sample of 29 sub-Saharan African countries in the period from 1981 to 2010 using the system GMM. The results show that both trade and financial openness lower growth volatility in the countries, though the effect of financial openness is not robust for alternative specifications.…”
Section: Financial Openness and Growth Volatilitymentioning
confidence: 99%